The Impact of Adding Stringer Elements to Barge Decks on Global Stress Values - Cindy Lionita Agusty; Alamsyah; Amalia Ika Wulandari; Wahyu Dhono Saputra (Politeknik Negeri Madura, 2025)
Ship construction includes three main types of construction, namely longitudinal construction, transverse construction, and mixed construction. The longitudinal construction of the ship is subjected to truss loads and is depicted in the rigid transverse joints of the ship with the aid of longitudinal beams. Senta side or stringer is a longitudinal support made of profile steel and faceplate, mounted on both sides of the inside of the ship's hull. There was a case of a barge with a broken hull because it did not have a side beam or stringer. This study aims to determine the maximum stress due to the addition of a side beam or stringer to the barge. The method used is finite element with the help of Ansys Mechanical Research software. In this study, the maximum stress that occurred on the 1 stringer barge was 96.96 N/mm² (hogging) and 62. 20 N/mm² (sagging). While on the 2 stringer barge it is 96.86 N/mm² (hogging) and 62.71 N/mm² (sagging). The percentage of voltage drop after the addition of a stringer is ± 30% with a safety factor in the range of 1.55 2.41.